Implementing Mumarasah Al-Lughah to Enhance Maharah Kalam Among Arabic Language Education Students: A Poac-Based Management Approach - Oktari, Sri Jomila; Mufidah, Nuril; Amrullah, Abdul Malik Karim (Abjadia : International Journal of Education, 2025)
This research aims to analyze the implementation of the mumarasah al-lughah program in improving the Arabic language skills of students of the Arabic Language Education Study Program (PBA) UIN Imam Bonjol Padang based on the classic management theory POAC (Planning, Organizing, Actuating, Controlling). The research used descriptive qualitative method, with the research subjects being PBA students of UIN Imam Bonjol Padang who participated in the mumarasah al-lughah program, the program committee, and other related parties totaling 30 people. Data collection techniques were conducted through in-depth interviews and official program documentation. Data analysis uses an inductive analysis model which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the mumarasah al-lughah program has been managed systematically according to the POAC principle (planning, organizing, implementing and supervising): program planning involves identifying student needs and preparing a curriculum based on communicative methods; organizing is done through the formation of an implementation team and division of tasks; program implementation includes routine Arabic language practice and guidance by experts; and supervision is carried out through periodic evaluation and continuous improvement. The implementation of POAC management is proven to contribute significantly in improving students' Arabic language skills, creating a conducive learning environment, and building students' confidence in communicating. The findings provide theoretical and practical contributions to the development of Arabic language learning programs in higher education, especially in the management of a POAC-based program.